Distribution of Giardia lamblia Genotypes in Children - Al-Ardi, Musafer H. (Iraqi Journal of Science, 2024)
The current study aimed to detect Giardia lamblia subtypes that infect children under 13 years and determine the association of subtype infection with some risk factors as age, gender, and residence. Triosephosphate isomerase gene from the positive microscopic samples was isolated. To confirm infection and the sensitivity of this gene, DNA in one negative and some positive samples were confirmed when amplified using β-giardin gene primers. From the 66 samples positive by microscopy, 65 tested positive by molecular assay of the triosephosphate isomerase gene with 98.4% sensitivity. While 37/65 (56.9%) represented subtype B, 23/65 (35.4%) represented subtype A, 5 (7.6%) represented A+B, while there was no E subtype. A subtype A in asymptomatic children exceeded 10/25 (40%) compared to 13/40 (32.5%) in symptomatic children. The proportion of B subtype among symptomatic children was higher than that of asymptomatic children (57.5% and 56% respectively). There was no significant difference between the subtype presence and gender, age or residence. Subtype A was higher in the watery diarrhoea samples than in the steatorrhea samples. On the contrary, B subtype was higher in the steatorrhea samples than in watery diarrhoea. Use of the gene triosephosphate isomerase showed a high sensitivity for molecular detection of Giardia spp. Children could be infected with both groups A and B subtypes. The study did not record any presence of subtype E. No significant difference between genders, age groups or place of residence was recorded. Symptoms and diarrhoea were insignificantly associated with subtype B.